PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN SIKAP PERCAYA DIRI PESERTA DIDIK KELAS III SEKOLAH DASAR - Mutiara Alma Umairoh (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2021)
This study aims to increase the self-confident attitude of grade III students of SD Negeri Grindang by applying the PBL learning model. This study is a Classroom Action Research (CAR) using the Kemmis and McTaggart model which includes the empanas of planning, implementation, observation, and reflection. The study included two cycle. Subject and subject data in this study were students of class III SD Negeri Grindang. This research uses collection and teaching techniques through observation, questionnaires and documentation. The data validity used source triangulation and data method triangulation. The data analysis technique used is an interactive analysis model. In pre-cycle, resulting in a percentage of 28,5% reaches the passing grade. The first cycle resulting in a percentage of 42,85% reaches the passing grade in classical terms, the second cycle resulting a percentage of 85% reaches the passing grade in classical terms. The conclusion in this study is the PBL learning model which can increase self-confidence in grade III students of SD Negeri Grindang for the 2020/2021 academic year.